Isozyme variations in some wheat genotypes in response to spot blotch infection - K.D. SRIVASTAVA and S.M.S. TOMAR*, SOMA DAS, RASHMI AGGARWAL (Indian Phytopathology, 2002)
The defense related enzymes (peroxidase and esterase) playa prominent role, either directly or indirectly in resistance responses. The enzyme activity was studied in resistant and susceptible genotypes, with or without Drechslera sorokiniana inoculation in one-week-old seedlings. High polymorphism was observed in PBW 343, Agra local and HD 2329 for both the enzymes while resistant Pusa-T 3336 showed low polymorphism. In healthy seedlings of Pusa-T 3336, 4 bands of peroxidase isozyme were obtained, where as in inoculated seedlings an extra band of Rmvalue 0.96 was obtained. In moderately resistant genotype, Bobwhite, 2 extra bands of peroxidase and 3 extra bands of esterase were obtained on challenge inoculation. Cluster analysis separated susceptible and moderately susceptible genotypes from resistant ones.